Der Westen als Wir-Gruppe im "Kampf der Kulturen" Diskursanalysen zu sprachlichen Konstruktionen der sozialen Welt - Kromminga, Jan-Henning (Diskursmuster / Discourse Patterns, 2022)
What is the "clash of civilizations"? What are us-group constructions? What is the West? This critical discourse analysis informed by cognitive linguistics answers these questions in detail using a data set comprising more than 100,000 German-language print media articles. It presents highly relevant findings on the use of "we" and "us," as well as on the media production of large social groups and political and cultural global conflicts.